Self-cementing properties of oil shale solid heat carrier retorting residue. Issue 6 (June 2013) - Talviste, Peeter; Sedman, Annette; Mõtlep, Riho; Kirsimäe, Kalle
Oil shale-type organic-rich sedimentary rocks can be pyrolysed to produce shale oil. The pyrolysis of oil shale using solid heat carrier (SHC) technology is accompanied by large amount of environmentally hazardous solid residue—black ash—which needs to be properly landfilled. Usage of oil shale is growing worldwide, and the employment of large SHC retorts increases the amount of black ash type of waste, but little is known about its physical and chemical properties. The objectives of this research were to study the composition and self-cementing properties of black ash by simulating different disposal strategies in order to find the most appropriate landfilling method. Three disposal methods were simulated in laboratory experiment: hydraulic disposal with and without grain size separation, and dry dumping of moist residue. Black ash exhibited good self-cementing properties with maximum compressive strength values of >6 MPa after 90 days. About 80% of strength was gained in 30 days. However, the coarse fraction (>125 µm) did not exhibit any cementation, thus the hydraulic disposal with grain size separation should be avoided. The study showed that self-cementing properties of black ash are governed by the hydration of secondary calcium silicates (e.g. belite), calcite and hydrocalumite.